Extensive conservation of ancient microsynteny across metazoans due to cis-regulatory constraints - Irimia, Manuel; Tena, Juan J.; Alexis, Maria S.; Fernandez-Miñan, Ana; Maeso, Ignacio; Bogdanović, Ozren; de la Calle-Mustienes, Elisa; Roy, Scott W.; Gómez-Skarmeta, José L.; Fraser, Hunter B. (Genome Research, 2012)
The order of genes in eukaryotic genomes has generally been assumed to be neutral, since gene order is largely scrambled over evolutionary time. Only a handful of exceptional examples are known, typically involving deeply conserved clusters of tandemly duplicated genes (e.g., Hox genes and histones). Here we report the first systematic survey of microsynteny conservation across metazoans, utilizing 17 genome sequences. We identified nearly 600 pairs of unrelated genes that have remained tightly physically linked in diverse lineages across over 600 million years of evolution. Integrating sequence conservation, gene expression data, gene function, epigenetic marks, and other genomic features, we provide extensive evidence that many conserved ancient linkages involve (1) the coordinated transcription of neighboring genes, or (2) genomic regulatory blocks (GRBs) in which transcriptional enhancers controlling developmental genes are contained within nearby bystander genes. In addition, we generated ChIP-seq data for key histone modifications in zebrafish embryos, which provided further evidence of putative GRBs in embryonic development. Finally, using chromosome conformation capture (3C) assays and stable transgenic experiments, we demonstrate that enhancers within bystander genes drive the expression of genes such as Otx and Islet, critical regulators of central nervous system development across bilaterians. These results suggest that ancient genomic functional associations are far more common than previously thought—involving ∼12% of the ancestral bilaterian genome—and that cis-regulatory constraints are crucial in determining metazoan genome architecture.